Positive electrode active material, its manufacturing method, and positive electrode and lithium secondary battery including the same

A lithium composite transition metal oxide with Al, Y, and Zr in single particles addresses the structural and performance issues of secondary particle electrodes, improving battery efficiency and stability through a specialized manufacturing process.

JP2025502227AActive Publication Date: 2025-01-24LG CHEM LTD

Patent Information

Application Number
JP2024541870
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-06-30
Filing Date
2023-06-28
Publication Date
2025-01-24
Estimated Expiration
2043-06-28

AI Technical Summary

Technical Problem

Existing positive electrode materials in the form of secondary particles for lithium secondary batteries face issues with gas generation, thermal stability, and increased fire risk due to high nickel content, along with low specific surface area and poor resistance characteristics.

Method used

A lithium composite transition metal oxide in the form of single particles, containing Al, Y, and Zr, with a specific composition and manufacturing process that includes primary and secondary firing, followed by a cobalt-containing coating, to enhance structural stability and electrochemical performance.

Benefits of technology

The solution improves the initial efficiency, resistance characteristics, and capacity of lithium secondary batteries by stabilizing the structure and reducing gas generation, thereby enhancing the battery's life characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025502227000001_ABST
    Figure 2025502227000001_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material in a single particle form, the positive electrode active material including a lithium composite transition metal oxide in a single particle form, the lithium composite transition metal oxide including Al, Y, and Zr, a method for producing the positive electrode active material, and a positive electrode and a lithium secondary battery including the positive electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0080870 filed on June 30, 2022, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to a positive electrode active material containing a lithium composite transition metal oxide in the form of a single particle, a method for producing the same, and a positive electrode and a lithium secondary battery containing the same. [Background technology]

[0003] Recently, the development of single particle cathode materials has been accelerated in order to solve the problems of the structure and thermal stability of the secondary particle cathode materials themselves. Specifically, when the secondary particle cathode materials are applied to lithium secondary batteries, there is a problem that a large amount of gas is generated, causing the volume of the battery to expand, and when the nickel content in the cathode material is increased to increase the capacity, there is a problem that the risk of fire also increases, so there is a growing need for the development of single particle cathode materials. However, single particle cathode materials have a problem of low specific surface area and poor resistance characteristics.

[0004] Therefore, there is a need to develop a single particle type positive electrode material that has excellent stability and can improve the initial efficiency and resistance characteristics of a battery when applied to the battery. Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention is an invention for solving the above problems, and has an object to provide a positive electrode active material containing a lithium transition metal composite oxide in a single particle form, which has excellent structural stability and can improve the initial efficiency, resistance characteristics, etc. of a battery when applied to the battery.

[0006] Another object of the present invention is to provide a method for producing the positive electrode active material.

[0007] Another object of the present invention is to provide a lithium secondary battery which contains the above positive electrode active material and has improved initial efficiency, resistance characteristics, and the like. [Means for solving the problem]

[0008] In order to solve the above problems, the present invention provides a positive electrode active material, a method for producing a positive electrode active material, a positive electrode, and a lithium secondary battery.

[0009] (1) The present invention provides a positive electrode active material that includes a lithium composite transition metal oxide in a single particle form, the lithium composite transition metal oxide including Al, Y, and Zr.

[0010] (2) In the present invention, in the above (1), the lithium transition metal oxide has an average particle size (D 50 ) is 2.5 μm to 5.5 μm.

[0011] (3) The present invention provides the positive electrode active material according to (1) or (2) above, wherein the Al is contained in an amount of 500 ppm to 3,000 ppm based on the total weight of the lithium composite transition metal oxide.

[0012] (4) The present invention provides the positive electrode active material according to any one of the above (1) to (3), wherein the Y is contained in an amount of 100 ppm to 2,000 ppm based on the total weight of the lithium composite transition metal oxide.

[0013] (5) The present invention provides the positive electrode active material according to any one of the above (1) to (4), wherein the Zr is contained in an amount of 500 ppm to 5,000 ppm based on the total weight of the lithium composite transition metal oxide.

[0014] (6) The present invention provides a positive electrode active material according to any one of the above (1) to (5), wherein the lithium transition metal oxide contains 60 mol % or more of nickel relative to the total number of moles of metals other than lithium.

[0015] (7) The present invention provides a positive electrode active material in any one of the above (1) to (6), wherein the lithium composite transition metal oxide has a composition represented by the following chemical formula 1: [Chemical formula 1] Li x [Ni a Co b Mn c Al d Y e Zr f M1 g ]O 2-y A y In the above Chemical Formula 1, M1 is one or more selected from B, Ti, W, Nb, Sr, Mo, Mg, P, V, Ta, Ga, and Ca; A is one or more selected from F, Cl, Br, I and S; 0.9≦x≦1.2, 0.6≦a<1, 0≦b≦0.4, 0≦c≦0.4, 0 <d≦0.01、0<e≦0.0006、0<f≦0.005、0≦g≦0.2、a+b+c+d+e+f+g=1、0≦y≦0.2である。

[0016] (8) The present invention provides a positive electrode active material according to any one of (1) to (7) above, further comprising a coating portion containing Co formed on the lithium composite transition metal oxide in the form of a single particle.

[0017] (9) The present invention provides the positive electrode active material according to (8) above, wherein the coating portion further contains Al, Zr, or a combination thereof.

[0018] (10) The present invention provides a method for producing a positive electrode active material, the method including the steps of: (A) mixing a positive electrode active material precursor, which is a composite transition metal hydroxide, a composite transition metal oxyhydroxide, or a combination thereof, a first lithium-containing raw material, an aluminum-containing raw material, an yttrium-containing raw material, and a zirconium-containing raw material to produce a mixture; (B) primary-firing the mixture at a temperature of 820°C to 950°C to produce a primary-firing product; and (C) selectively mixing a second lithium-containing raw material with the primary-firing product, followed by secondary-firing at a temperature of 700°C to 850°C to produce a secondary-firing product.

[0019] (11) The present invention provides the method for producing a positive electrode active material according to (10), further comprising, before the step (C), (B') a step of pulverizing the primary fired product.

[0020] (12) The present invention provides the method for producing a positive electrode active material according to (10) or (11), further comprising the step (C') of pulverizing the secondary fired product.

[0021] (13) The present invention provides the method for producing a positive electrode active material according to any one of (10) to (12), further comprising the step of (D) mixing the secondary fired product with a cobalt-containing coating material and then heat-treating the mixture.

[0022] (14) The present invention provides the method for producing a positive electrode active material according to (13), wherein when the secondary fired product and the cobalt-containing coating material are mixed in step (D), an aluminum-containing coating material, a zirconium-containing coating material, or a combination thereof is further mixed.

[0023] (15) The present invention provides the method for producing a positive electrode active material according to the above (13) or (14), wherein the cobalt-containing coating material is mixed in an amount such that a ratio (B / A) of the number of moles of cobalt contained in the cobalt-containing coating material (B) to the total number of moles of metals other than lithium contained in the secondary fired product (A) is 0.01 to 0.03.

[0024] (16) The present invention provides the method for producing a positive electrode active material according to (14), wherein the aluminum-containing coating material is mixed in an amount of 0.03 to 0.10 parts by weight based on 100 parts by weight of the secondary fired product.

[0025] (17) The present invention provides the method for producing a positive electrode active material according to any one of the above (13) to (16), wherein the heat treatment is carried out in an oxygen atmosphere.

[0026] (18) The present invention provides the method for producing a positive electrode active material according to any one of the above (13) to (17), wherein the heat treatment is carried out at a temperature of 600°C to 800°C.

[0027] (19) The present invention provides a positive electrode comprising the positive electrode active material according to any one of (1) to (9) above.

[0028] (20) The present invention provides a lithium secondary battery comprising the positive electrode according to (19) above, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte. Effect of the Invention

[0029] The positive electrode active material of the present invention includes a lithium composite transition metal oxide in the form of a single particle, and the lithium composite transition metal oxide includes Al, Y, and Zr, and can improve the initial efficiency, resistance characteristics, capacity characteristics, life characteristics, etc. of a lithium secondary battery.

[0030] Moreover, according to the method for producing a positive electrode active material of the present invention, the above-mentioned positive electrode active material can be produced effectively. [Brief description of the drawings]

[0031] [Figure 1] 1 shows TEM EDX-Mapping data of the positive electrode active material of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0032] The present invention will now be described in further detail in order to facilitate understanding of the present invention.

[0033] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of ​​the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.

[0034] In this specification, the terms "comprise", "comprise", "have" and the like are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, but are not intended to preclude the presence or additional possibility of one or more different features, numbers, steps, components, or combinations thereof.

[0035] As used herein, the term "on" is meant to include not only cases where one structure is formed immediately on top of another structure, but also cases where a third structure is interposed between the structures.

[0036] In this specification, the term "single-particle positive electrode active material" refers to a positive electrode active material consisting of 10 or less primary particles, as opposed to a spherical secondary particle positive electrode active material produced by a conventional method, which is formed by agglomeration of tens to hundreds of primary particles. Specifically, in the present invention, the single-particle positive electrode active material may be a single particle consisting of one primary particle, or may be a secondary particle formed by agglomeration of several primary particles.

[0037] The term "primary particle" refers to the smallest particle unit that can be recognized when observing a positive electrode active material through a scanning electron microscope, and the term "secondary particle" refers to a secondary structure formed by aggregation of a plurality of primary particles.

[0038] As used herein, the term “average particle size (D 50The "average particle size" refers to the particle size at the 50% point of the cumulative volume distribution by particle size. The average particle size is determined by dispersing the powder to be measured in a dispersion medium, introducing it into a commercially available laser diffraction particle size measuring device (e.g., S3500 manufactured by Microtrac), measuring the difference in the diffraction pattern due to the particle size when the particles pass through a laser beam, calculating the particle size distribution, and calculating the particle size at the 50% point of the cumulative volume distribution by particle size in the measuring device. 50 can be measured.

[0039] positive electrode active material The present invention provides a positive electrode active material including a lithium composite transition metal oxide in a single particle form, the lithium composite transition metal oxide including Al, Y, and Zr. The lithium composite transition metal oxide may have a layered structure.

[0040] The present inventors have found that when a positive electrode active material contains a lithium composite transition metal oxide in a single particle form, and the lithium composite transition metal oxide contains Al, Y, and Zr as dopants, the structural stability of the positive electrode active material is increased, cation mixing is reduced, and the grain size is large, about 500 nm to 4 μm, and the initial efficiency, resistance characteristics, capacity characteristics, life characteristics, etc. of a lithium secondary battery can be improved, and have completed the present invention. Specifically, the present inventors have found that, due to the structural stability of a positive electrode active material in a single particle form with a small average particle size, Zr and Al are contained as dopants, and when Al is contained as a dopant, there is a problem that the grain size does not become large, but in order to solve this problem, the present invention has been completed by simultaneously containing Y.

[0041] According to the present invention, the lithium composite transition metal oxide in the form of a single particle has an average particle size (D 50 The average particle diameter (D) of the lithium composite transition metal oxide may be 2.5 μm to 5.5 μm, specifically, 2.5 μm or more, or 3.0 μm or more, and 4.5 μm or less, or 5.5 μm or less. 50When the average particle diameter (D 50 If the thickness is less than 2.5 μm, there are problems in that the battery life characteristics are reduced and the amount of gas generated is increased, whereas if the thickness exceeds 5.5 μm, there are problems in that the capacity characteristics and resistance characteristics of the battery are reduced.

[0042] According to the present invention, the Al may be contained in an amount of 500 ppm to 3,000 ppm based on the total weight of the lithium composite transition metal oxide, whereby the internal crystal structure of the positive electrode active material is stabilized, and the capacity and resistance characteristics of the battery can be improved.

[0043] According to the present invention, the Y may be contained in an amount of 100 ppm to 2,000 ppm based on the total weight of the lithium composite transition metal oxide. In this case, the grain size of one particle satisfies about 500 nm to 4 μm, and the capacity characteristic and life characteristic of the battery can be improved.

[0044] According to the present invention, the Zr may be contained in an amount of 500 ppm to 5,000 ppm based on the total weight of the lithium composite transition metal oxide. In this case, Zr is stably doped into the lithium layer, improving structural stability during lithium insertion and extraction, thereby improving the life and resistance characteristics of the battery.

[0045] According to the present invention, the lithium composite transition metal oxide may contain nickel in an amount of 60 mol% or more, specifically 80 mol% or more, more specifically 85 mol% or more, based on the total moles of metals other than lithium. That is, the lithium composite transition metal oxide may be a high nickel (High Ni)-based lithium composite transition metal oxide. In this case, the energy density of a lithium secondary battery may be improved.

[0046] According to the present invention, the lithium composite transition metal oxide may have a composition represented by the following Chemical Formula 1. In this case, the lithium composite transition metal oxide has a layered structure.

[0047] [Chemical formula 1] Li x [Ni a Co b Mn c Al d Y e Zr f M1 g ]O 2-y A y

[0048] In the above Chemical Formula 1, M1 is one or more selected from B, Ti, W, Nb, Sr, Mo, Mg, P, V, Ta, Ga, and Ca; A is one or more selected from F, Cl, Br, I and S; 0.9≦x≦1.2, 0.6≦a<1, 0≦b≦0.4, 0≦c≦0.4, 0 <d≦0.01、0<e≦0.0006、0<f≦0.005、0≦g≦0.2、a+b+c+d+e+f+g=1、0≦y≦0.2である。

[0049] The a means the atomic fraction of nickel among the metal elements in the lithium composite transition metal oxide, and may be 0.6≦a<1, 0.8≦a≦0.98, or 0.85≦a≦0.95.

[0050] The b represents the atomic fraction of cobalt among the metal elements in the lithium composite transition metal oxide, and may be 0≦b≦0.4, 0.01≦b≦0.2, or 0.01≦b≦0.15.

[0051] The c represents the atomic fraction of manganese among the metal elements in the lithium composite transition metal oxide, and may be 0≦c≦0.4, 0.01≦c≦0.2, or 0.01≦c≦0.15.

[0052] The d represents the atomic fraction of aluminum among the metal elements in the lithium composite transition metal oxide, and is 0 <d≦0.01、0.002≦d≦0.008または0.003≦d≦0.006であることができる。

[0053] The e represents the atomic fraction of yttrium among the metal elements in the lithium composite transition metal oxide, and is 0 <e≦0.0006、0.0001≦e≦0.0005または0.0002≦e≦0.0003であることができる。

[0054] The f represents the atomic fraction of zirconium among the metal elements in the lithium composite transition metal oxide, and is 0 <f≦0.005、0.001≦f≦0.003または0.001≦f≦0.002であることができる。

[0055] The g means the atomic fraction of the M1 element among the metal elements in the lithium composite transition metal oxide, and may be 0≦g≦0.2, 0≦g≦0.1, or 0≦g≦0.05.

[0056] According to the present invention, the positive electrode active material may further include a coating portion including Co formed on the single particle lithium composite transition metal oxide. The coating portion may further include Al, Zr, or a combination thereof. When the positive electrode active material further includes the coating portion, the amount of residual lithium by-products may be reduced, structural stability may be increased, and the life characteristics and resistance characteristics of the battery may be improved, and the amount of gas generation may be reduced. Here, the coating portion may have a thin film form and may be formed entirely or locally on the lithium composite transition metal oxide.

[0057] The Co present in the coating portion may be included in an amount of 0.5 mol % to 3 mol % based on the total moles of metals other than lithium contained in the lithium composite transition metal oxide, whereby residual lithium by-products can be further reduced, and life and resistance characteristics can be further improved.

[0058] The Al present in the coating portion may be included in an amount of 300 ppm to 10,000 ppm based on the total weight of the lithium composite transition metal oxide, which may increase the structural stability and further improve the life characteristics, resistance characteristics, etc.

[0059] Method for producing positive electrode active material The present invention provides a method for producing the above-mentioned positive electrode active material. That is, the positive electrode active material according to the present invention is produced by the following method for producing a positive electrode active material.

[0060] The method for producing a positive electrode active material according to the present invention includes the steps of (A) mixing a positive electrode active material precursor, which is a composite transition metal hydroxide, a composite transition metal oxyhydroxide, or a combination thereof, a first lithium-containing raw material, an aluminum-containing raw material, an yttrium-containing raw material, and a zirconium-containing raw material to produce a mixture, (B) primarily firing the mixture at a temperature of 820°C to 950°C to produce a primary fired product, and (C) selectively mixing a second lithium-containing raw material with the primary fired product, and then secondary firing at a temperature of 700°C to 850°C to produce a secondary fired product.

[0061] The aluminum-containing raw material may be at least one selected from Al(OH)3, Al2O3, AlCl3, Al(NO)3, AlSO4, and Al2S3, specifically at least one selected from Al(OH)3, Al2O3, and Al(NO)3, more specifically Al(OH)3. The aluminum-containing raw material may be added in an amount of 500 ppm to 3,000 ppm based on the total weight of the positive electrode active material precursor.

[0062] The yttrium-containing raw material may be at least one selected from YCl3, Y2O3, Y(NO3)3, Y(OH)3, YSZ, Y2(SO4)3, and Y2S3, specifically at least one selected from Y2O3 and Y(OH)3, more specifically Y2O3. The yttrium-containing raw material may be added in an amount of 100 ppm to 2000 ppm based on the total weight of the positive electrode active material precursor.

[0063] The zirconium-containing source material is Zr(OH)4, ZrO2, Zr(NO3)4, ZrCl4, ZrS2, Zr(SO4)2 and C8H 12 The zirconium-containing raw material may be one or more selected from Zr(OH)4 and ZrO2, more specifically, ZrO2. The zirconium-containing raw material may be added in a content of 500 ppm to 5000 ppm based on the total weight of the positive electrode active material precursor.

[0064] When the mixture is primarily fired at a temperature of 820° C. to 950° C., the primary particles of the positive electrode active material precursor are aggregated to produce a primarily fired product in the form of single particles.

[0065] When the primary firing temperature is within the above range, the primary particles of the positive electrode active material precursor aggregate to form a primary fired product having a structurally stable single particle form. When the primary firing temperature is less than 820° C., the primary particles may not aggregate sufficiently, and when it exceeds 950° C., a structurally unstable fired product having a low crystallinity may be produced.

[0066] According to the present invention, the primary firing may be performed in an oxygen atmosphere in order to prevent the lithium transition metal oxide from degenerating into a rock salt structure.

[0067] According to the present invention, the primary firing can be carried out for 3 to 12 hours, specifically 6 to 12 hours, and more specifically 9 to 12 hours, in order to aggregate the primary particles and improve the crystallinity of the primary fired product.

[0068] The primary fired product is subjected to secondary firing at a temperature of 700° C. to 850° C., whereby lithium is inserted into the primary fired product to produce a secondary fired product, which is a lithium transition metal composite oxide in the form of a single particle.

[0069] When the secondary firing temperature is within the above range, lithium is inserted into the rock salt structure that may be formed on the surface of the primary firing product due to the high temperature during the primary firing, restoring the layered structure, and there is an advantage in that lithium by-products are reduced. On the other hand, when the secondary firing temperature is less than 700°C, there is a problem that the lithium insertion rate is slow due to the low temperature, and when it exceeds 850°C, there is a problem that the surface of the primary firing product degenerates into a rock salt structure due to the high temperature, and lithium by-products remain.

[0070] According to the present invention, the secondary firing may be performed in an oxygen atmosphere in order to prevent the lithium transition metal oxide from degenerating into a rock salt structure.

[0071] According to the present invention, the secondary baking can be carried out for 3 hours to 12 hours, specifically 6 hours to 12 hours, and more specifically 9 hours to 12 hours, in order to increase the crystallinity of the crystal structure inside the positive electrode active material.

[0072] The method for producing a positive electrode active material according to the present invention may further include, before the step (C), a step (B') of pulverizing the primary sintered product. The step (B') includes pulverizing the primary sintered product into particles having an average particle size (D 50 ) can be pulverized to a size of 2.5 μm to 5.5 μm.

[0073] The method for producing a positive electrode active material according to the present invention may further include (C') a step of pulverizing the secondary fired product. The step (C') includes pulverizing the primary fired product to a mean particle size (D 50 ) can be pulverized to a size of 2.5 μm to 5.5 μm.

[0074] The pulverization in steps (B') and (C') can be carried out using a pin mill, ACM, jet mill, etc. Meanwhile, the pin mill can be carried out under conditions of 18,000 rpm, the ACM can be carried out using equipment manufactured by Hosokawa under conditions of classification at 6,000 rpm and pulverization at 12,000 rpm, and the jet mill can be carried out using equipment manufactured by ZM solution under conditions of pulverization pressure of 6 bar and classification at 3,500 rpm.

[0075] The positive electrode active material according to the present invention may be prepared by a process of adding the lithium-containing raw material in two separate steps or a process of adding the lithium-containing raw material at once, that is, the lithium-containing raw material may be added all at once before the primary firing, or may be added separately before the primary firing and before the secondary firing.

[0076] In the case where the lithium-containing raw material is added in two separate portions, the positive electrode active material according to the present invention can be prepared by, for example, first sintering the mixture prepared in step (A) at a temperature of 820° C. to 950° C. to obtain a first sintered product, and then sintering the first sintered product at room temperature to obtain an average particle size (D 50 The crushed primary sintered product is mixed with the second lithium-containing raw material and then subjected to secondary sintering at a temperature of 700°C to 850°C to obtain a secondary sintered product. The secondary sintered product is then crushed at room temperature to obtain an average particle size (D 50 The first lithium-containing raw material may be prepared by pulverizing the first lithium-containing raw material to a particle size of 2.5 μm to 5.5 μm. In this regard, in the step (A), the first lithium-containing raw material may be mixed so that the ratio (M:Li) of the total number of moles (M) of transition metals contained in the positive electrode active material precursor to the number of moles (Li) of lithium contained in the first lithium-containing raw material is 1:0.95 to 1:1.02, and in the step (C), the second lithium-containing raw material may be mixed so that the ratio (M:Li) of the total number of moles (M) of transition metals contained in the positive electrode active material precursor in the step (A) to the number of moles (Li) of lithium contained in the second lithium-containing raw material is 1:0.01 to 1:1.10.

[0077] In the case where the lithium-containing raw material is added at once, the positive electrode active material according to the present invention can be prepared by, for example, first firing the mixture prepared in step (A) at a temperature of 820° C. to 950° C., immediately lowering the temperature to 700° C. to 850° C. (without lowering the temperature to room temperature), and second firing at a temperature of 700° C. to 850° C. to obtain a second fired product, and then sintering the second fired product at room temperature to obtain an average particle size (D 50 ) to 2.5 μm to 5.5 μm. Here, in the step (A), the first lithium-containing raw material may be mixed such that the ratio (M:Li) of the total moles (M) of transition metals contained in the positive electrode active material precursor to the moles (Li) of lithium contained in the first lithium-containing raw material is 1:1.00 to 1:1.10. The primary firing temperature may be higher than the secondary firing temperature.

[0078] The method for preparing a positive electrode active material according to the present invention may further include (D) a step of mixing the secondary sintered product and a cobalt-containing coating material and then heat-treating the mixture, in which case a coating portion containing Co is formed on the secondary sintered product (a lithium transition metal composite oxide in the form of a single particle).

[0079] According to the present invention, in step (D), when the secondary fired product and the cobalt-containing coating material are mixed, an aluminum-containing coating material, a zirconium-containing coating material, or a combination thereof may be further mixed in. In this case, the coating portion may further contain Al, Zr, or a combination thereof in addition to Co.

[0080] According to the present invention, the cobalt-containing coating material may be mixed in an amount such that the ratio (B / A) of the number of moles of cobalt (B) contained in the cobalt-containing coating material to the total number of moles (A) of metals other than lithium contained in the secondary fired product is 0.01 to 0.03. In this case, there is an advantage that lithium by-products can be controlled in a manufacturing process of a positive electrode active material that does not include a water washing process.

[0081] The cobalt-containing coating material may be one or more selected from Co(OH)2, Co3O4, CoO, (CH3CO2)2Co, CoCl2, and CoSO4·xH2O, and may be Co(OH)2.

[0082] According to the present invention, the aluminum-containing coating material may be mixed in an amount of 0.03 to 0.10 parts by weight based on 100 parts by weight of the secondary fired product, thereby improving the lifespan, resistance, and gas generation amount by ensuring structural stability.

[0083] The aluminum-containing coating material may be one or more selected from Al(OH)3, Al2(SO4)3·xH2O, Al2O3, Al(NO3)3·9H2O, AlCl3, and C2H5O4Al, and may be specifically Al(OH)3.

[0084] The zirconium-containing coating materials include Zr(OH)4, ZrO2, Zr(NO3)4, ZrCl4, ZrS2, Zr(SO4)2 and C8H 12 O8Zr.

[0085] According to the present invention, the heat treatment may be carried out in an oxygen atmosphere to prevent the lithium transition metal oxide from degenerating into a rock salt structure.

[0086] According to the present invention, the heat treatment can be performed at a temperature of 600°C to 800°C, specifically 650°C to 780°C, and more specifically 680°C to 720°C, so that the coating portion is formed to an appropriate thickness.

[0087] According to the present invention, the heat treatment can be carried out for 1 hour to 10 hours, specifically 2 hours to 8 hours, and more specifically 3 hours to 6 hours in order to increase the crystallinity of the coating portion.

[0088] positive electrode The present invention provides a positive electrode comprising the positive electrode active material.

[0089] The positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, and the positive electrode active material layer may include the positive electrode active material.

[0090] The positive electrode current collector may contain a metal having high conductivity, and is not particularly limited as long as the positive electrode active material layer is easily attached and is non-reactive in the voltage range of the battery. The positive electrode current collector may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may have a thickness of typically 3 μm to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0091] The positive electrode active material layer may selectively include a conductive material and a binder, if necessary, together with the positive electrode active material. Here, the positive electrode active material may be included in an amount of 80 wt% to 99 wt%, more specifically, 85 wt% to 98.5 wt%, based on the total weight of the positive electrode active material layer, and within this range, excellent capacity characteristics may be exhibited.

[0092] The conductive material is used to give conductivity to the electrode, and can be used without any particular limitation as long as it does not cause a chemical change in the battery and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive tubes such as carbon nanotubes; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and among these, one type alone or a mixture of two or more types can be used. The conductive material can be contained in 0.1% by weight to 15% by weight based on the total weight of the positive electrode active material layer.

[0093] The binder serves to improve adhesion between particles of the positive electrode active material and adhesion between the positive electrode active material and the current collector.Specific examples of the binder include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylalcohol, polyacrylonitrile, polymethyl methacrylate, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, polymers in which hydrogen is substituted with Li, Na, or Ca, or various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 0.1% by weight to 15% by weight based on the total weight of the positive electrode active material layer.

[0094] The positive electrode can be manufactured by a normal positive electrode manufacturing method, except for using the positive electrode active material. Specifically, the positive electrode can be manufactured by applying a positive electrode active material layer forming composition, which is prepared by dissolving or dispersing the positive electrode active material and, if necessary, a binder, a conductive material, and a dispersant in a solvent, onto a positive electrode current collector, and then drying and rolling the composition, or by casting the positive electrode active material layer forming composition onto another support, and then laminating the film obtained by peeling the composition from the support onto a positive electrode current collector.

[0095] The solvent may be a solvent commonly used in the art, and may include dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), dimethylformamide (DMF), acetone, water, etc., and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, binder, and dispersant in consideration of the coating thickness of the slurry and the manufacturing yield, and to have a viscosity that can show excellent thickness uniformity when applied to manufacture a positive electrode.

[0096] Lithium secondary battery The present invention provides a lithium secondary battery including the positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte.

[0097] The lithium secondary battery may optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and a separator, and a sealing member that seals the battery container.

[0098] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0099] The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may have a thickness of usually 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0100] The negative electrode active material layer may optionally contain a binder and a conductive material in addition to the negative electrode active material.

[0101] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β(0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites and Sn-C composites, and any one or a mixture of two or more of these may be used. In addition, a thin film of metallic lithium may be used as the negative electrode active material. In addition, both low-crystalline carbon and high-crystalline carbon may be used as the carbon material. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes. The negative electrode active material may be included in an amount of 80 wt% to 99 wt% based on the total weight of the negative electrode active material layer.

[0102] The binder of the negative electrode active material layer is a component that helps to bond between the conductive material, the active material, and the current collector, and is usually added in an amount of 0.1% by weight to 10% by weight based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.

[0103] The conductive material of the negative electrode active material layer is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 10% by weight or less, preferably 5% by weight or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples of such conductive materials include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.

[0104] The negative electrode may be manufactured by applying a composition for forming a negative electrode active material layer, which is prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent, onto a negative electrode current collector and drying the composition. Alternatively, the negative electrode may be manufactured by casting the composition for forming a negative electrode active material layer onto a separate support, peeling it off from the support, and laminating the resulting film onto the negative electrode current collector.

[0105] The separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is generally used as a separator in a lithium secondary battery can be used without any particular limitation. In particular, a separator that has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability is preferable. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof can be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. can be used. In addition, a coated separator containing a ceramic component or a polymeric material can be used to ensure heat resistance or mechanical strength, and can be selectively used as a single layer or multilayer structure.

[0106] The electrolyte may include, but is not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc. that can be used in manufacturing a lithium secondary battery. As a specific example, the electrolyte may include an organic solvent and a lithium salt.

[0107] The organic solvent can be used without any particular limitation as long as it can act as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent can be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene or fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvents that can be used include carbonate-based solvents such as polycarbonate (PC) and polycarbonate-based solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can enhance the charge / discharge performance of a battery and a low-viscosity straight-chain carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred.

[0108] The lithium salt can be used without any particular limitation as long as it is a compound that can provide lithium ions used in lithium secondary batteries. Specifically, the anion of the lithium salt is F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - The lithium salt may be at least one selected from the group consisting of LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The lithium salt is preferably used in a concentration range of 0.1M to 2.0M. When the lithium salt concentration is within the above range, the electrolyte has appropriate conductivity and viscosity, so that it can exhibit excellent electrolyte performance and lithium ions can move effectively.

[0109] In addition to the constituents of the electrolyte, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethyl alcohol amine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethyl alcohol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in the capacity of the battery, improving the discharge capacity of the battery, etc. Here, the additives may be contained in an amount of 0.1% by weight to 5% by weight based on the total weight of the electrolyte.

[0110] The lithium secondary battery including the positive electrode active material according to the present invention exhibits excellent initial efficiency, resistance characteristics, capacity characteristics, and life characteristics, and is therefore useful in portable devices such as mobile phones, notebook computers, and digital cameras, and in the field of electric vehicles such as hybrid electric vehicles (HEVs) and electric vehicles (EVs).

[0111] The external shape of the lithium secondary battery of the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.

[0112] The lithium secondary battery according to the present invention can be used as a battery cell used as a power source for a small device, and can also be preferably used as a unit battery in a medium- to large-sized battery module including a large number of battery cells.

[0113] Thus, a battery module including the lithium secondary battery as a unit cell and a battery pack including the same are provided.

[0114] The battery module or the battery pack may be used as a power source for one or more medium- to large-sized devices, such as a power tool; an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.

[0115] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to exemplary embodiments thereof, so that those skilled in the art can easily practice the present invention. However, the present invention may be embodied in many different forms and should not be construed as limited to the embodiments set forth herein. EXAMPLES

[0116] Examples and Comparative Examples Example 1 Composite transition metal hydroxides in the form of secondary particles formed by the aggregation of tens to hundreds of primary particles (composition: Ni 0.885 Co 0.035 Mn 0.08 (OH)2, average particle size (D 50 A mixture was prepared by mixing Al(OH)3 (manufactured by Dazhou KC Co., Ltd.) in an amount of 1400 ppm based on the total weight of the composite transition metal hydroxide, Y2O3 (manufactured by Neo Performance Co., Ltd.) in an amount of 1000 ppm based on the total weight of the composite transition metal hydroxide, and ZrO2 (manufactured by R&F Co., Ltd.) in an amount of 1500 ppm based on the total weight of the composite transition metal hydroxide, and mixing the mixture.

[0117] The mixture was first fired at 830°C for 6 hours to obtain a first fired product, and the first fired product was then subjected to a granular sintering process at room temperature to obtain a powder with an average particle size (D 50 ) was ground to 3.8 μm.

[0118] The crushed primary calcined product and LiOH were mixed so that the ratio of the total number of moles of transition metals (Ni+Co+Mn) contained in the composite transition metal hydroxide to the number of moles of lithium (Li) contained in LiOH ((Ni+Co+Mn):Li) was 1:0.04, and the secondary calcination was performed at 760°C for 9 hours to obtain a secondary calcined product. The secondary calcined product was then crushed at room temperature to obtain a powder with an average particle size (D 50 A single particle form of lithium composite transition metal oxide (composition: LiNi 0.87836 Co 0.03493 Mn 0.07985 Al 0.00499 Y 0.00027 Zr 0.0016 O2) was obtained.

[0119] The lithium composite transition metal oxide in the form of single particles, Co(OH)2 (manufactured by Huayou Co., Ltd.) and Al(OH)3 (manufactured by Dazhou KC Co., Ltd.) were uniformly mixed, and then heat-treated in an oxygen atmosphere at a temperature of 700°C for 5 hours to obtain a positive electrode active material (composition: LiNi 0.85761 Co 0.05489 Mn 0.07978 Al 0.00586 Y 0.00027 Zr 0.00159 Here, the Co(OH)2 was mixed in an amount such that the ratio (B / A) of the number of moles of cobalt (B) contained in the cobalt-containing coating material to the total number of moles of metals other than lithium (A) contained in the single particle lithium composite transition metal oxide was 0.02, and the Al(OH)3 was mixed in an amount of 0.05 parts by weight with respect to 100 parts by weight of the single particle lithium composite transition metal oxide.

[0120] Example 2 Composite transition metal hydroxides in the form of secondary particles formed by the aggregation of tens to hundreds of primary particles (composition: Ni 0.885 Co 0.035 Mn 0.08 (OH)2, average particle size (D 50A mixture was prepared by mixing Al(OH)3 (manufactured by Dazhou KC Co., Ltd.) in an amount of 1400 ppm based on the total weight of the composite transition metal hydroxide, Y2O3 (manufactured by Neo Performance Co., Ltd.) in an amount of 2000 ppm based on the total weight of the composite transition metal hydroxide, and ZrO2 (manufactured by R&F Co., Ltd.) in an amount of 1500 ppm based on the total weight of the composite transition metal hydroxide, and mixing the mixture.

[0121] The mixture was first fired at 830°C for 6 hours to obtain a first fired product, and the first fired product was then subjected to a granular sintering process at room temperature to obtain a powder with an average particle size (D 50 ) was ground to 3.8 μm.

[0122] The crushed primary calcined product and LiOH were mixed so that the ratio of the total number of moles of transition metals (Ni+Co+Mn) contained in the composite transition metal hydroxide to the number of moles of lithium (Li) contained in LiOH ((Ni+Co+Mn):Li) was 1:0.04, and the secondary calcination was performed at 760°C for 9 hours to obtain a secondary calcined product. The secondary calcined product was then crushed at room temperature to obtain a powder with an average particle size (D 50 A single particle form of lithium composite transition metal oxide (composition: LiNi 0.87813 Co 0.03492 Mn 0.07983 Al 0.00499 Y 0.00054 Zr 0.00159 O2) was obtained.

[0123] The lithium composite transition metal oxide in the form of single particles, Co(OH)2 (manufactured by Huayou Co., Ltd.) and Al(OH)3 (manufactured by Dazhou KC Co., Ltd.) were uniformly mixed, and then heat-treated in an oxygen atmosphere at a temperature of 700°C for 5 hours to obtain a positive electrode active material (composition: LiNi 0.85738 Co 0.05487 Mn 0.07976 Al 0.00586 Y 0.00054 Zr 0.00159Here, the Co(OH)2 was mixed in an amount such that the ratio (B / A) of the number of moles of cobalt (B) contained in the cobalt-containing coating material to the total number of moles of metals other than lithium (A) contained in the single particle lithium composite transition metal oxide was 0.02, and the Al(OH)3 was mixed in an amount of 0.05 parts by weight with respect to 100 parts by weight of the single particle lithium composite transition metal oxide.

[0124] Example 3 Composite transition metal hydroxides in the form of secondary particles formed by the aggregation of tens to hundreds of primary particles (composition: Ni 0.885 Co 0.035 Mn 0.08 (OH)2, average particle size (D 50 A mixture was prepared by mixing Al(OH)3 (manufactured by Dazhou KC Co., Ltd.) in an amount of 2800 ppm based on the total weight of the composite transition metal hydroxide, Y2O3 (manufactured by Neo Performance Co., Ltd.) in an amount of 1000 ppm based on the total weight of the composite transition metal hydroxide, and ZrO2 (manufactured by R&F Co., Ltd.) in an amount of 1500 ppm based on the total weight of the composite transition metal hydroxide, and mixing the mixture.

[0125] The mixture was first fired at 830°C for 6 hours to obtain a first fired product, and the first fired product was then subjected to a granular sintering process at room temperature to obtain a powder with an average particle size (D 50 ) was ground to 3.8 μm.

[0126] The crushed primary calcined product and LiOH were mixed so that the ratio of the total number of moles of transition metals (Ni+Co+Mn) contained in the composite transition metal hydroxide to the number of moles of lithium (Li) contained in LiOH ((Ni+Co+Mn):Li) was 1:0.04, and the secondary calcination was performed at 760°C for 9 hours to obtain a secondary calcined product. The secondary calcined product was then crushed at room temperature to obtain a powder with an average particle size (D 50 A single particle form of lithium composite transition metal oxide (composition: LiNi 0.87338 Co 0.03493Mn 0.07985 Al 0.00998 Y 0.00027 Zr 0.00159 O2) was obtained.

[0127] The lithium composite transition metal oxide in the form of single particles, Co(OH)2 (manufactured by Huayou Co., Ltd.) and Al(OH)3 (manufactured by Dazhou KC Co., Ltd.) were uniformly mixed, and then heat-treated in an oxygen atmosphere at a temperature of 700°C for 5 hours to obtain a positive electrode active material (composition: LiNi 0.85262 Co 0.05489 Mn 0.07978 Al 0.01085 Y 0.00027 Zr 0.00159 Here, the Co(OH)2 was mixed in an amount such that the ratio (B / A) of the number of moles of cobalt (B) contained in the cobalt-containing coating material to the total number of moles of metals other than lithium (A) contained in the single particle lithium composite transition metal oxide was 0.02, and the Al(OH)3 was mixed in an amount of 0.05 parts by weight with respect to 100 parts by weight of the single particle lithium composite transition metal oxide.

[0128] Example 4 Composite transition metal hydroxides in the form of secondary particles formed by the aggregation of tens to hundreds of primary particles (composition: Ni 0.885 Co 0.035 Mn 0.08 (OH)2, average particle size (D 50 A mixture was prepared by mixing Al(OH)3 (manufactured by Dazhou KC Co., Ltd.) in an amount of 1400 ppm based on the total weight of the composite transition metal hydroxide, Y2O3 (manufactured by Neo Performance Co., Ltd.) in an amount of 1000 ppm based on the total weight of the composite transition metal hydroxide, and ZrO2 (manufactured by R&F Co., Ltd.) in an amount of 3500 ppm based on the total weight of the composite transition metal hydroxide, and mixing the mixture.

[0129] The mixture was first fired at 830°C for 6 hours to obtain a first fired product, and the first fired product was then subjected to a granular sintering process at room temperature to obtain a powder with an average particle size (D 50 ) was ground to 3.8 μm.

[0130] The crushed primary calcined product and LiOH were mixed so that the ratio of the total number of moles of transition metals (Ni+Co+Mn) contained in the composite transition metal hydroxide to the number of moles of lithium (Li) contained in LiOH ((Ni+Co+Mn):Li) was 1:0.04, and the secondary calcination was performed at 760°C for 9 hours to obtain a secondary calcined product. The secondary calcined product was then crushed at room temperature to obtain a powder with an average particle size (D 50 A single particle form of lithium composite transition metal oxide (composition: LiNi 0.87651 Co 0.03486 Mn 0.07968 Al 0.00498 Y 0.00027 Zr 0.0037 O2) was obtained.

[0131] The lithium composite transition metal oxide in the form of single particles, Co(OH)2 (manufactured by Huayou Co., Ltd.) and Al(OH)3 (manufactured by Dazhou KC Co., Ltd.) were uniformly mixed, and then heat-treated in an oxygen atmosphere at a temperature of 700°C for 5 hours to obtain a positive electrode active material (composition: LiNi 0.85576 Co 0.05481 Mn 0.07961 Al 0.00585 Y 0.00027 Zr 0.0037 Here, the Co(OH)2 was mixed in an amount such that the ratio (B / A) of the number of moles of cobalt (B) contained in the cobalt-containing coating material to the total number of moles of metals other than lithium (A) contained in the single particle lithium composite transition metal oxide was 0.02, and the Al(OH)3 was mixed in an amount of 0.05 parts by weight with respect to 100 parts by weight of the single particle lithium composite transition metal oxide.

[0132] Comparative Example 1 Composite transition metal hydroxides in the form of secondary particles formed by the aggregation of tens to hundreds of primary particles (composition: Ni 0.885 Co0.035 Mn 0.08 (OH)2, average particle size (D 50 A mixture was prepared by mixing LiOH and Al(OH)3 (manufactured by Dazhou KC Co., Ltd.) in an amount of 1400 ppm based on the total weight of the composite transition metal hydroxide and ZrO2 (manufactured by R&F Co., Ltd.) in an amount of 1500 ppm based on the total weight of the composite transition metal hydroxide.

[0133] The mixture was first fired at 830°C for 6 hours to obtain a first fired product, and the first fired product was then subjected to a granular sintering process at room temperature to obtain a powder with an average particle size (D 50 ) was ground to 3.8 μm.

[0134] The crushed primary calcined product and LiOH were mixed so that the ratio of the total number of moles of transition metals (Ni+Co+Mn) contained in the composite transition metal hydroxide to the number of moles of lithium (Li) contained in LiOH ((Ni+Co+Mn):Li) was 1:0.04, and the secondary calcination was performed at 760°C for 9 hours to obtain a secondary calcined product. The secondary calcined product was then crushed at room temperature to obtain a powder with an average particle size (D 50 A single particle form of lithium composite transition metal oxide (composition: LiNi 0.8786 Co 0.03494 Mn 0.07987 Al 0.00499 Zr 0.0016 O2) was obtained.

[0135] The lithium composite transition metal oxide in the form of single particles, Co(OH)2 (manufactured by Huayou Co., Ltd.) and Al(OH)3 (manufactured by Dazhou KC Co., Ltd.) were uniformly mixed, and then heat-treated in an oxygen atmosphere at a temperature of 700°C for 5 hours to obtain a positive electrode active material (composition: LiNi 0.85784 Co 0.0549 Mn 0.0798 Al 0.00586 Zr 0.0016Here, the Co(OH)2 was mixed in an amount such that the ratio (B / A) of the number of moles of cobalt (B) contained in the cobalt-containing coating material to the total number of moles of metals other than lithium (A) contained in the single particle lithium composite transition metal oxide was 0.02, and the Al(OH)3 was mixed in an amount of 0.05 parts by weight with respect to 100 parts by weight of the single particle lithium composite transition metal oxide.

[0136] Comparative Example 2 Composite transition metal hydroxides in the form of secondary particles formed by the aggregation of tens to hundreds of primary particles (composition: Ni 0.885 Co 0.035 Mn 0.08 (OH)2, average particle size (D 50 A mixture was produced by mixing LiOH and Y2O3 (manufactured by Neo Performance) in an amount of 1000 ppm based on the total weight of the composite transition metal hydroxide and ZrO2 (manufactured by R&F) in an amount of 1500 ppm based on the total weight of the composite transition metal hydroxide.

[0137] The mixture was first fired at 830°C for 6 hours to obtain a first fired product, and the first fired product was then subjected to a granular sintering process at room temperature to obtain a powder with an average particle size (D 50 ) was ground to 3.8 μm.

[0138] The crushed primary calcined product and LiOH were mixed so that the ratio of the total number of moles of transition metals (Ni+Co+Mn) contained in the composite transition metal hydroxide to the number of moles of lithium (Li) contained in LiOH ((Ni+Co+Mn):Li) was 1:0.04, and the secondary calcination was performed at 760°C for 9 hours to obtain a secondary calcined product. The secondary calcined product was then crushed at room temperature to obtain a powder with an average particle size (D 50 A single particle form of lithium composite transition metal oxide (composition: LiNi 0.88336 Co 0.03493 Mn 0.07985 Y 0.00027 Zr 0.00159O2) was obtained.

[0139] The lithium composite transition metal oxide in the form of single particles, Co(OH)2 (manufactured by Huayou Co., Ltd.) and Al(OH)3 (manufactured by Dazhou KC Co., Ltd.) were uniformly mixed, and then heat-treated in an oxygen atmosphere at a temperature of 700°C for 5 hours to obtain a positive electrode active material (composition: LiNi 0.86259 Co 0.05489 Mn 0.07978 Al 0.00088 Y 0.00027 Zr 0.00159 Here, the Co(OH)2 was mixed in an amount such that the ratio (B / A) of the number of moles of cobalt (B) contained in the cobalt-containing coating material to the total number of moles of metals other than lithium (A) contained in the single particle lithium composite transition metal oxide was 0.02, and the Al(OH)3 was mixed in an amount of 0.05 parts by weight with respect to 100 parts by weight of the single particle lithium composite transition metal oxide.

[0140] Comparative Example 3 Composite transition metal hydroxides in the form of secondary particles formed by the aggregation of tens to hundreds of primary particles (composition: Ni 0.885 Co 0.035 Mn 0.08 (OH)2, average particle size (D 50 A mixture was prepared by mixing LiOH and Al(OH)3 (manufactured by Dazhou KC Co., Ltd.) in an amount of 1400 ppm based on the total weight of the composite transition metal hydroxide and Y2O3 (manufactured by Neo Performance Co., Ltd.) in an amount of 1000 ppm based on the total weight of the composite transition metal hydroxide.

[0141] The mixture was first fired at 830°C for 6 hours to obtain a first fired product, and the first fired product was then subjected to a granular sintering process at room temperature to obtain a powder with an average particle size (D 50 ) was ground to 3.8 μm.

[0142] The crushed primary calcined product and LiOH were mixed so that the ratio of the total number of moles of transition metals (Ni+Co+Mn) contained in the composite transition metal hydroxide to the number of moles of lithium (Li) contained in LiOH ((Ni+Co+Mn):Li) was 1:0.04, and the secondary calcination was performed at 760°C for 9 hours to obtain a secondary calcined product. The secondary calcined product was then crushed at room temperature to obtain a powder with an average particle size (D 50 A single particle form of lithium composite transition metal oxide (composition: LiNi 0.87976 Co 0.03499 Mn 0.07998 Al 0.005 Y 0.00027 O2) was obtained.

[0143] The lithium composite transition metal oxide in the form of single particles, Co(OH)2 (manufactured by Huayou Co., Ltd.) and Al(OH)3 (manufactured by Dazhou KC Co., Ltd.) were uniformly mixed, and then heat-treated in an oxygen atmosphere at a temperature of 700°C for 5 hours to obtain a positive electrode active material (composition: LiNi 0.85901 Co 0.05494 Mn 0.07991 Al 0.00587 Y 0.00027 Here, the Co(OH)2 was mixed in an amount such that the ratio (B / A) of the number of moles of cobalt (B) contained in the cobalt-containing coating material to the total number of moles of metals other than lithium (A) contained in the single particle lithium composite transition metal oxide was 0.02, and the Al(OH)3 was mixed in an amount of 0.05 parts by weight with respect to 100 parts by weight of the single particle lithium composite transition metal oxide.

[0144] Experimental Example Experimental Example 1: Analysis of Positive Electrode Active Material In order to confirm how the dopants Al, Y, and Zr are present in the positive electrode active material prepared in Example 1 and how the coating portion containing Co and Al is formed, a TEM (Transmission Electron Microscope) (Titan Buved G2 600-300) EDX-Mapping was used for analysis, and the TEM EDX-Mapping data is shown in FIG. 1.

[0145] Referring to FIG. 1, in the case of the positive electrode active material prepared in Example 1, it can be seen that the dopants Al, Y, and Zr do not have a concentration gradient within the particles and are uniformly distributed, and that a coating portion containing Co and Al is formed on the surface of the particles in the form of a thin film.

[0146] Experimental Example 2: Confirmation of the amount of residual lithium present in the secondary fired product The amount of residual lithium present in each of the secondary fired products produced in Examples 1 to 4 and Comparative Examples 1 to 3, that is, the contents of Li2CO3 and LiOH, were confirmed by the following method.

[0147] Specifically, 5 g of each of the secondary fired products produced in Examples 1 to 4 and Comparative Examples 1 to 3 was added to 100 g of distilled water, mixed for 5 minutes, and then filtered. After filtering, the amounts of Li2CO3 and LiOH dissolved in the distilled water were measured by titration (using 0.1N HCl) using a pH meter, and the results are shown in Table 1.

[0148] [Table 1]

[0149] Experimental Example 3: Evaluation of battery characteristics The positive electrode active materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3, carbon black conductive material, and polyvinylidene fluoride (PVDF) binder were mixed in a ratio of 96:2:2 in N-methylpyrrolidone (NMP) solvent to prepare positive electrode slurry. The positive electrode slurry was applied to one side of an aluminum current collector, dried at 150°C, and rolled to prepare a positive electrode.

[0150] A lithium metal electrode was used as the negative electrode, and a porous polyethylene separator was interposed between the positive and negative electrodes to prepare an electrode assembly, which was then placed inside a battery case and an electrolyte was injected into the case to prepare a half-cell. The electrolyte was prepared by dissolving 1.0M LiPF6 in an organic solvent in which ethylene carbonate (EC): ethyl methyl carbonate (EMC): diethyl carbonate (DEC) were mixed in a volume ratio of 3:4:3.

[0151] Each half-cell thus prepared was charged at 0.1C in CC-CV mode at 25°C up to 4.3V, and discharged at a constant current of 0.1C down to 3.0V, while measuring the initial charge capacity and initial discharge capacity, and the initial efficiency and direct current internal resistance (DCIR) were calculated, which are shown in Table 2 below. For reference, the initial efficiency value is the percentage value of the initial discharge capacity relative to the initial charge capacity, and the DCIR value is a value calculated by dividing the difference between the voltage at 60 seconds and the initial voltage while discharging at a constant current of 0.1C by the applied current.

[0152] The capacity of the lithium secondary battery was measured by repeating 50 charge / discharge cycles at 45°C and in the range of 3.0 to 4.25V at a constant current of 0.33C, and the percentage of the discharge capacity at the 50th cycle to the discharge capacity at the first cycle was taken as the capacity retention rate, which is shown in Table 2 below. The resistance increase rate was taken as the percentage of DCIR obtained by dividing the voltage drop (ΔV) for 60 seconds in the 50th discharge cycle by the current to DCIR obtained by dividing the voltage drop (ΔV) for 60 seconds in the first discharge cycle by the current, which is shown in Table 2 below.

[0153] [Table 2]

[0154] Referring to Table 2, it can be seen that in the case of the batteries including the positive electrode active materials of Examples 1 to 4, the initial efficiency and capacity retention rate are high, and the initial resistance and resistance increase rate are low.

[0155] In comparison, the positive electrode active material of Comparative Example 1 does not contain Y, so there is a problem with grain growth, and it can be confirmed that the initial efficiency and capacity retention characteristics of the battery containing this are reduced. In addition, the positive electrode active material of Comparative Example 2 does not contain Al, so there are high defects and the cation mixing is increased, so it can be confirmed that the initial efficiency and capacity retention characteristics of the battery containing this are reduced. In addition, the positive electrode active material of Comparative Example 3 does not contain Zr that maintains structural stability, so it can be confirmed that the initial resistance and resistance increase rate are high.

Claims

1. A lithium transition metal composite oxide in the form of a single particle is included, The lithium transition metal oxide comprises Al, Y, and Zr.

2. The lithium transition metal oxide has an average particle size (D 50 2. The positive electrode active material according to claim 1, wherein the average particle diameter is 2.5 μm to 5.5 μm.

3. The positive electrode active material according to claim 1, wherein the Al is contained in an amount of 500 ppm to 3,000 ppm based on the total weight of the lithium composite transition metal oxide.

4. The positive electrode active material according to claim 1 , wherein the Y is contained in an amount of 100 ppm to 2,000 ppm based on the total weight of the lithium composite transition metal oxide.

5. The positive electrode active material according to claim 1 , wherein the Zr is contained in an amount of 500 ppm to 5,000 ppm based on the total weight of the lithium composite transition metal oxide.

6. The positive electrode active material according to claim 1 , wherein the lithium composite transition metal oxide contains 60 mol % or more of nickel relative to the total number of moles of metals other than lithium.

7. The positive electrode active material according to claim 1 , wherein the lithium composite transition metal oxide has a composition represented by the following Chemical Formula 1: [Chemical formula 1] Li x [Ni a Co b Mn c Al d Y e Zr f M1 g ]O 2-y A y In the above Chemical Formula 1, M1 is one or more selected from B, Ti, W, Nb, Sr, Mo, Mg, P, V, Ta, Ga and Ca; A is one or more selected from F, Cl, Br, I and S; 0.9≦x≦1.2, 0.6≦a<1, 0≦b≦0.4, 0≦c≦0.4, 0<d≦0.01, 0<e≦0.0006, 0<f≦0.005, 0≦g≦0.2, a+b+c+d+e+f+g=1, and 0≦y≦0.

2.

8. The positive electrode active material of claim 1 , further comprising a coating portion including Co formed on the single particle lithium composite transition metal oxide.

9. The positive electrode active material of claim 8 , wherein the coating portion further comprises Al, Zr, or a combination thereof.

10. (A) mixing a positive electrode active material precursor, which is a composite transition metal hydroxide, a composite transition metal oxyhydroxide, or a combination thereof, a first lithium-containing raw material, an aluminum-containing raw material, an yttrium-containing raw material, and a zirconium-containing raw material to produce a mixture; (B) primary firing the mixture at a temperature of 820°C to 950°C to produce a primary fired product; (C) selectively mixing a second lithium-containing raw material with the primary fired product, and then secondary firing at a temperature of 700° C. to 850° C. to produce a secondary fired product.

11. The method for producing a positive electrode active material according to claim 10, further comprising, before the step (C), (B') a step of pulverizing the primary fired product.

12. The method for producing a positive electrode active material according to claim 10, further comprising the step of (C') pulverizing the secondary fired product.

13. The method for producing a positive electrode active material according to claim 10, further comprising the step of (D) performing a heat treatment after mixing the secondary fired product with the cobalt-containing coating material.

14. The method of claim 13, wherein when mixing the secondary fired product with the cobalt-containing coating material in step (D), an aluminum-containing coating material, a zirconium-containing coating material, or a combination thereof is further mixed.

15. The cobalt-containing coating material is mixed in an amount such that the ratio (B / A) of the number of moles of cobalt (B) contained in the cobalt-containing coating material to the total number of moles (A) of metals other than lithium contained in the secondary fired product is 0.01 to 0.

03. The method for producing a positive electrode active material according to claim 13.

16. The method for producing a positive electrode active material according to claim 14, wherein the aluminum-containing coating material is mixed in an amount of 0.03 to 0.10 parts by weight based on 100 parts by weight of the secondary fired product.

17. The method for producing a positive electrode active material according to claim 13 , wherein the heat treatment is carried out in an oxygen atmosphere.

18. The method for producing a positive electrode active material according to claim 13, wherein the heat treatment is carried out at a temperature of 600° C. to 800° C.

19. A positive electrode comprising the positive electrode active material according to any one of claims 1 to 9.

20. The positive electrode according to claim 19 ; A negative electrode; a separator interposed between the positive electrode and the negative electrode; and an electrolyte.

Citation Information

Patent Citations

  • Cathode active material for lithium secondary battery, method for manufacturing same, cathode comprising same for lithium secondary battery, and lithium secondary battery

    EP3761415A1

  • Method for manufacturing positive electrode active material for secondary battery and positive electrode active material for secondary battery manufactured by the same

    JP2019508869A

  • Positive electrode active material for secondary battery, method for producing the same, and lithium secondary battery including the same

    JP2021516424A

  • Positive electrode active material for lithium secondary battery, method for producing the same, positive electrode for lithium secondary battery including the same, and lithium secondary battery

    JP2021520035A

  • Secondary battery, electronic device, vehicle, and method for producing positive electrode active material

    WO2022034414A1

Cited By

  • Positive electrode active material, preparation method thereof, positive electrode including the same, and rechargeable lithium batteries

    JP2025083330A

  • Positive electrode active material for lithium secondary batteries and lithium secondary batteries containing the same

    JP2026518562A

  • Positive electrode active material for lithium ion secondary battery, positive electrode for lithium ion secondary battery, and lithium ion secondary battery

    WO2026205577A1

  • Positive electrode active material for lithium ion secondary battery, positive electrode for lithium ion secondary battery, and lithium ion secondary battery

    WO2026205578A1